Interaction Entre l’Evaluation de l’Entreprise et la Gouvernance Cas de la Société Saidal - TLAMSI Ismahene née DRAOU (My University, 2018)
The major changes that have taken place in the world economy in particular; globalization, the importance of financial exchanges, the opening of the market and the multiplication of transactions, have made the evaluation of the company and the governance, two determining devices within an organization. In this work, our objectives are the study, on the one hand, of the governance within an company, through its various mechanisms, on the other hand, the evaluation of the company, by the different techniques commonly used. In terms of results, we first showed that there is a reciprocal relationship between business valuation and governance. Thus, corporate governance can have a positive effect on value, on the one hand, and, the valuation of the company, can be used as an instrument that helps managers in steering their business, another side.